Infratentorial Supracerebellar Approach for Resection of Midbrain Cavernous Malformation: 3-Dimensional Operative Video. Issue 2 (4th June 2019) - Patel, Krunal; Budohoski, Karol P; Olijnyk, Leonardo Desessards; Bulstrode, Harry; Santarius, Thomas; Kirollos, Ramez W; Trivedi, Rikin A
Abstract: Cavernous malformations (cavernomas) of the brain stem with recurrent hemorrhage may be amenable to microsurgical resection if they are present close to the surface. The risks of surgery need to be balanced with the natural history of the lesion and the accumulation of neurological deficits and risk to life with multiple hemorrhages. In this 3D operative video, we illustrate the technique for the resection of a dorsally located midbrain cavernous malformation. Informed consent was obtained for this procedure. The cavernoma is accessed with the use of a supracerebellar infratentorial approach. The infratentorial craniotomy and coagulation of the superior vermian veins is shown. A description is provided of the use of hemosiderin staining and the intercollicular relative "safe zone" 1 as landmarks for the neurotomy. The technique of cavernoma dissection from the surrounding gliotic plane is shown and described. In this case, the patient required prolonged rehabilitation but fully recovered without residual deficit 1 yr following surgery.